2006
DOI: 10.2166/wst.2006.515
|View full text |Cite
|
Sign up to set email alerts
|

Start-up and steady-state results of a full-scale UASB reactor treating malting wastewater

Abstract: An Imhoff tank was reconstructed into a 250 m3 UASB reactor in order to treat a malting plant wastewater. The UASB was inoculated with sludge from an anaerobic lagoon used for slaughterhouse wastewater treatment. After two months of operation the reactor achieved full load with an HRT of 17 h, a COD removal higher than 80% and a biogas production of 300 m3/day (77% average methane content), with an organic loading rate of 3.6 kgCOD/m3.d (0.24 kgCOD/kgVSS.d). A yield coefficient of 0.09 gVSS/gCODrem was found f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
4
11
0
Order By: Relevance
“…A full scale UASB reactor of 250 m 3 [10] for treatment of malting plant effluent was monitored during 180 days (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A full scale UASB reactor of 250 m 3 [10] for treatment of malting plant effluent was monitored during 180 days (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…In this case, it is difficult to reach true steady states because of inlet flow and concentration disturbances. Another approach is proposed in this paper based on global COD balances from S 1 and S 2 , applied to a 250-m 3 reactor treating malting plant effluent [10]. After k 1 , k 2 , k 3 and k 6 determination, an asymptotic observer [11] is used to estimate biomass concentration without knowledge about the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…A full scale (250 m 3 ) UASB reactor (Borzacconi et al 2006) was inoculated with sludge taken from an anaerobic lagoon used for the treatment of slaughterhouse effluents. The amount of sludge used was 3900 kg of TSS with an average content of 77% VSS (3,000 kg) and with a SMA of 0.1 gCOD/gVSS.d.…”
Section: Methodsmentioning
confidence: 99%
“…In previous works results from the full scale and a pilot experiences were reported (Martínez et al 2001;Borzacconi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This has led to organisations constructing AD plants to achieve various waste management targets and renewable energy goals (Bekkering et al, 2016) A popular form of treatment for medium to high strength effluents is Upflow Anaerobic Sludge Blankets (UASBs) (Musee et al, 2016), which have demonstrated high reliability both in terms of their COD removal efficiencies (typically >80%) and biogas CH 4 concentrations (typically >50%) (Latif et al, 2011). This performance has been documented in a number of studies treating a wide range of wastewaters including: Palm oil mill effluent (Siang, 2006); Paper mill wastewater (Kamali et al, 2016); Distillery wastewater (Musee et al, 2016); dairy wastewater (Tawfik et al, 2008); fishery wastewater (Huang et al, 2009); slaughterhouse wastewater (Chavez et al, 2005); Piggery effluent (Huang et al, 2005) municipal wastewater (Rivzi et al, 2015), malting's steep water (Borzacconi et al, 2006) and malt ingredients factory wastewater (Cairns and Mead, 2017).…”
Section: Introductionmentioning
confidence: 97%